Relationship between triglyceride glucose index and the incidence of non-alcoholic fatty liver disease in the elderly: a retrospective cohort study in China. Issue 11 (27th November 2020) - Huanan, Chen; Sangsang, Li; Amoah, Adwoa Nyantakyiwaa; Yacong, Bo; Xuejiao, Chen; Zhan, Shi; Guodong, Wan; Jian, Huang; Songhe, Shi; Quanjun, Lyu
Abstract : Objective: Non-alcoholic fatty liver disease (NAFLD) is one of the major causes of liver-related diseases but relationship between triglyceride glucose (TyG) and NAFLD in the elderly is not reported yet. In this study, we investigated the role of TyG index for predicting the incidence of NAFLD in the elderly. Design and setting: This is a prospective cohort study in Henan, China, from 2011 to 2018. Participants and methods: In total, 46 693 elderly who participated in a routine physical examination programme from 2011 to 2018 were included in this study. TyG index was calculated as ln (fasting triglyceride (mg/dL)×fasting plasma glucose (mg/dL)/2), while NAFLD was defined as hepatic steatosis after excluding other causes based on the results of abdominal ultrasonography; Cox regression model was performed to explore the relationship between TyG index and NAFLD. Also, mediation effect was used to analyse the role of the TyG index in WHtR (waist-to-height ratio) and NAFLD. Results: During the 149 041 person-years follow-up, a total of 5660 NAFLD events occurred (3.80/100 person-years). After adjusting for potential confounding factors, quartiles 4 of TyG index significantly increased the incidence of NAFLD compared with quartile 1, the HRs and 95% CI were 1.314 (1.234 to 1.457). In addition, TyG index played a partial mediating role in the relationship between WHtR and NAFLD and indirect effect was 1.009 (1.006 to 1.011). Conclusion: Higher TyG index was associated with higher risk of NAFLD in the aged, and therefore, TyG index may be a novel predictor for incidence of NAFLD. Further, regular examination and evaluation of the TyG index might be useful for controlling the occurrence of NAFLD.